Influenza A infection enhances antigen‐induced airway inflammation and hyperresponsiveness in young but not aged mice. Issue 9 (September 2014) - Birmingham, J. M.; Gillespie, V. L.; Srivastava, K.; Li, X‐M.; Busse, P. J.
Summary Background Although morbidity and mortality rates from asthma are highest in patients > 65 years of age, the effect of older age on airway inflammation in asthma is not well established. Objective To investigate age‐related differences in the promotion of allergic inflammation after influenza A viral respiratory infection on antigen‐specific IgE production, antigen‐induced airway inflammation and airway hyperresponsiveness in mice. Methods To accomplish this objective, the following model system was used. Young (6 week) and aged (18 months) BALB/c mice were first infected with a non‐lethal dose of influenza virus A (H/HKx31). Mice were then ovalbumin (OVA)‐sensitized during the acute infection (3‐days post inoculation) and then chronically underwent challenge to the airways with OVA. Forty‐eight hours after the final OVA challenge, airway hyperresponsiveness (AHR), bronchoalveolar fluid (BALF) cellular and cytokine profile, antigen‐specific IgE and IgG1, and lung tissue inflammation were measured. Results Age‐specific differences were noted on the effect of a viral infection, allergic sensitization, airway inflammation and airway hyperresponsiveness. Serum OVA‐specific IgE was significantly increased in only the aged mice infected with influenza virus. Despite greater morbidity (e.g. weight loss and sickness scores) during the acute infection in the 18‐month old mice that were OVA‐sensitized, there was little effect on the AHR and BALF cellular differential. In contrast, BALF neutrophils and AHR increased, but eosinophils decreased in 6‐week mice that were OVA‐sensitized during an acute influenza infection. Conclusion With increased age in a mouse model, viral infection prior to antigen sensitization affects the airway and systemic allergic response differently. These differences may reflect distinct phenotypic features of allergic inflammation in older patients with asthma.